Does prospectus information matter in IPO pricing?. Issue 4 (9th July 2018) - Mohd-Rashid, Rasidah; Masih, Mansur; Abdul-Rahim, Ruzita; Che-Yahya, Norliza
Abstract : Purpose: The purpose of this study is to identify selected information from the prospectus that might signal the initial public offering (IPO) offer price. Design/methodology/approach: This study uses cross-sectional data for a 14-year period from 2000 to 2014 in examining hypotheses relating to Shariah -compliant status, institutional investors, underwriter ranking and shareholder retention, with respect to their associations with the offer price of the IPOs. Further, this study uses ordinary least squares (OLS) for all models, including the models for both subsamples of Shariah - and non- Shariah -compliant IPOs. As for robustness, this study incorporates the quantile regression and quadratic model. Findings: The results tend to provide support for the argument that firms with Shariah -compliant status reflect lower uncertainty and project better signalling of quality due to greater scrutiny by the government and thus are able to offer IPOs at higher prices. Similarly, firms with a higher proportion of shareholder retention indicate lower risks as insiders forego their options to diversify their portfolio, and hence could price their IPOs higher. Finally, the involvement of institutional investors and higher underwriter ranking could be used by firms to disregard information asymmetry, and therefore, the issuer might have to discount the IPO offer price. Research limitations/implications: This study focuses solely on information in the prospectus that should not be disregarded by the investors in valuing the appropriateness of the IPO offer price. This study contributes in terms of providing a better understanding of the determinant factors of the IPO offer price of the firms which are Shariah- compliant. Originality/value: This paper provides evidence for the determinants of the IPO offer price in a fixed pricing mechanism for both Shariah -and non- Shariah -compliant IPOs.